2017
DOI: 10.1099/mic.0.000436
|View full text |Cite
|
Sign up to set email alerts
|

MazEF toxin-antitoxin proteins alter Escherichia coli cell morphology and infrastructure during persister formation and regrowth

Abstract: When exposed to antibiotics, many bacteria respond by activating intracellular 'toxin' proteins, which arrest cell growth and induce formation of persister cells that survive antibiotics. After antibiotics are removed, persisters can regrow by synthesizing 'antitoxin' proteins that sequester toxin proteins. In Escherichia coli, MazE antitoxin sequesters the activity of MazF toxin, which extensively cleaves cellular RNAs. Although the functions of MazEF proteins are well characterized, there is surprisingly lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
2
23
1
Order By: Relevance
“…Furthermore, the elongation followed by death phenotype seen with some persister cells (Figure 2C) indicates that classic methods to determine persister cell activity do not fully reflect the short-term viability of the whole persister population as these cells would fail to form a colony. Moreover, the elongation of the rifampicin-induced persister cells on agarose pads during 360 resuscitation is similar to the cell elongation seen previously in a persister cell with high guanosine tetraphosphate levels (Maisonneuve et al, 2013) and persister cells formed by production of toxin MazF of the MazF/MazE toxin/antitoxin system (Cho et al, 2017); this latter phenotype was seen with ciprofloxacin. Combined with our observations, cell elongation during persister waking is a common phenotype that is not restricted to the use of ampicillin to form persister cells via corruption of cell wall 365 synthesis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the elongation followed by death phenotype seen with some persister cells (Figure 2C) indicates that classic methods to determine persister cell activity do not fully reflect the short-term viability of the whole persister population as these cells would fail to form a colony. Moreover, the elongation of the rifampicin-induced persister cells on agarose pads during 360 resuscitation is similar to the cell elongation seen previously in a persister cell with high guanosine tetraphosphate levels (Maisonneuve et al, 2013) and persister cells formed by production of toxin MazF of the MazF/MazE toxin/antitoxin system (Cho et al, 2017); this latter phenotype was seen with ciprofloxacin. Combined with our observations, cell elongation during persister waking is a common phenotype that is not restricted to the use of ampicillin to form persister cells via corruption of cell wall 365 synthesis.…”
Section: Discussionsupporting
confidence: 85%
“…Unfortunately, 45 stationary phase cells consist of antibiotic-sensitive cells, tolerant cells, and persister cells, and persister cells are the smallest population. Furthermore, persister cells are not identical to stationary-phase tolerant cells based on transmission electron microscopy which shows a cell structure for each cell type (Cho et al, 2017). These results also illustrate the need for persister cell populations in which persister cells are the dominant cell type in order to more accurately estimate the persister cell wake time.…”
Section: Introductionmentioning
confidence: 94%
“…C) indicates that classic methods to determine persister cell activity do not fully reflect the short‐term viability of the whole persister population as these cells would fail to form a colony. Moreover, the elongation of the rifampicin‐induced persister cells on agarose pads during resuscitation is similar to the cell elongation seen previously in a persister cell with high guanosine tetraphosphate levels (Maisonneuve et al ., ) and persister cells formed by production of toxin MazF of the MazF/MazE toxin/antitoxin system (Cho et al ., ); this latter phenotype was seen with ciprofloxacin. Combined with our observations, cell elongation during persister waking is a common phenotype that is not restricted to the use of ampicillin to form persister cells via corruption of cell wall synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, stationary phase cells consist of antibiotic‐sensitive cells, tolerant cells and persister cells and persister cells are the smallest population. Furthermore, persister cells are not identical to stationary‐phase tolerant cells based on transmission electron microscopy which shows a cell structure for each cell type (Cho et al ., ). These results illustrate the need for persister cell populations in which persister cells are the dominant cell type in order to more accurately estimate the persister cell wake time.…”
Section: Introductionmentioning
confidence: 99%
“…5g of reference 19, after treatment with potassium cyanide and ampicillin, persister cells are not created since the population continues to decrease with time without the biphasic pattern that is typical of persistence; instead, a pattern consistent with tolerance is seen since the viable cell population continues to decrease. Indeed, previous authors utilizing stationary cells recognize this population as tolerant, not as persister cells (13, 20, 21), and transmission electron microscopy has demonstrated that persister cells are phenotypically distinct from stationary-phase cells (22). Hence, stationary-phase cells are not persister cells.…”
Section: Opinion/hypothesismentioning
confidence: 95%